Birokrasi SAMSAT Tantangan Penggunaan Teknologi (KIOS-K) dalam Mempercepat Proses Administrasi - Dini Putri Dwina N; Irfan Sophan Himawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The application of technology in public services, especially in the Oiterne-Stop Manunggal Administration System (SAMSAT), aims to increase bureaucratic efficiency and transparency. However, the realization of accelerating administrative processes through digital innovation still faces various challenges. This study aims to analyze the obstacles faced in the use of technology in the SAMSAT bureaucracy, both from the internal side of the institution and from the perspective of service users. The research method used is a descriptive qualitative approach with interview techniques and documentation studies of several SAMSAT offices in urban areas. The results of the study show that the main challenges include the limitations of technological infrastructure, the resistance of the apparatus to digital changes, and the lack of digital literacy in some communities. In addition, it was found that technology systems that have not been optimally integrated have slowed down the service process. This study recommends the need for continuous training, improved integrated digital systems, and more effective communication strategies to the public to maximize the role of technology in SAMSAT bureaucratic reform.